Pulmonary vein isolation durability with fluoroscopy or 3D mapping-guided radiofrequency balloon ablation: a mandated remap study - Alexandre Almorad; Alvise Del Monte; Domenico Giovanni Della Rocca; Luigi Pannone; Charles Audiat; Roberto Scacciavillani; Lorenzo Marcon; Kazutaka Nakasone; Giampaolo Vetta; Ingrid Overeinder; Gezim Bala; Antonio Sorgente; et al. (Frontiers in Cardiovascular Medicine)
BackgroundEffective balloon positionnking during pulmonary vein isolation (PVI) with a radiofrequency balloon (RFB) is crucial for optimal energy delivery, maximising lesion formation, and preventing gaps. Traditionally, fluoroscopy is used to guide pulmonary vein (PV) occlusion, however, this method exposes patients to radiation. Recently, RFBs equipped with 3D electroanatomical mapping (EAM) offer an alternative approach, potentially achieving the same results with reduced radiation exposure. Our main aim was to evaluate procedural characteristics, such as acute isolation and time-to-isolation (TTI), when the RFB is positioned based only on fluoroscopy feedback vs. fluoroscopy and a 3D-EAM. The secondary objective was to assess PVI durability through mandated remapping in asymptomatic patients from both groups.MethodsA total of 60 patients were enrolled and underwent either a fluoroscopy-guided (FLUO, 30 patients) or fluoroscopy + 3D-EAM (3D-MAP, 30 patients) ablation. In each group, 15 patients without any documented recurrence underwent protocol-mandated repeat 3D-EAM six months after the index ablation. Procedural outcomes, lesion metrics, and safety profiles were assessed and compared between groups.ResultsAt a median follow-up of 579 days, freedom from any atrial tachyarrhythmias (ATAs) was 89.7% in the FLUO group and 92.3% in the 3D-EAM group (P > 0.05). The latter was associated with significantly reduced fluoroscopy exposure (median 10.5 vs. 7.0 min, P < 0.005). Procedure time and efficacy metrics, including single-shot isolation rates and TTI, were comparable between groups. Durable PVI on a per PV basis was present in 54/60 (90%) vs. 57/60 (94%) of PVs in the FLUO and 3D-EAM groups, respectively (P = 0.9).ConclusionRadiofrequency balloon led to a high rate of durable PVI whether its guided by fluoroscopy only or 3D mapping. The latter allowed avoiding dye comsuption and a reduction of fluoroscopic times.